A Survey on Security of Web Services and its Implementations - Shridevi S.; Deepti Gautam (EAI Endorsed Transactions on Cloud Systems, 2017)
Web Services are software snippets that can be integrated in HTTP and XML based messages based on web technology. Security plays a crucial role in web services. Web services provide a basis for system integration without any programming language and operating system constraint. The security of web services are determined by the secrecy and reliability of the XML based SOAP message that are used for communication. The valuable data stored on computers and servers over the internet need to be secured based on information security features. The security of web services is an important part and security algorithms using encryption techniques are implemented in web services for key generation and encryption of the messages in SOAP and RESTful Services, to provide more secure communication between two electronic devices. Our work focuses on a systematic study on the security features provided by SOAP and RESTful Services and tries to address the different issues faced in security and presents the research scope in the area of web security